Pengaruh Struktur Modal, Pertumbuhan Penjualan dan Financial Risk Terhadap Nilai Perusahaan - Wilujeng, Fadhila; Atmaja, Sri Nitta Crissiana Wirya (CV. Rayyan Dwi Bharata, 2024)
This research is Assosiatif research, the data used is secondary data in the form of financial reports. This research aims to analyze and obtain empirical evidence regarding the influence of capital structure, sales growth and financial risk on company value in consumer non-cyclical companies listed on the Indonesia Stock Exchange (BEI) 2018-2022. The population used in this research is Consumer Non-Cylicals companies listed on the Indonesia Stock Exchange (BEI) in 2018-2022. The number of samples in this research was 13 companies obtained through purposive sampling. Obtained 65 data. The data analysis technique used is panel data regression using the help of Eviews version 12 SV software. The test results show that simultaneously capital structure, sales growth and financial risk influence company value. Then, partially, capital structure and while financial risk has an effect on company value, and sales growth has no effect on company value,